2005
DOI: 10.1017/s0376892905002146
|View full text |Cite
|
Sign up to set email alerts
|

A framework for understanding community resident perceptions of Masoala National Park, Madagascar

Abstract: Protected areas (PAs) represent a central strategy in biodiversity conservation worldwide. Yet many PAs are weakened by people-PA conflicts resulting from the separation of natural resource protection from human considerations. Research at Masoala National Park in Madagascar focused on the following questions: (1) What are the factors that influence residents' perceptions of the Park and restrictions on use of natural resources in the Park area? (2) How do residents of communities on the periphery of the Park … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
113
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 31 publications
5
113
0
8
Order By: Relevance
“…Protected areas (PAs) have been considered as a key to biodiversity conservation [1][2][3][4]. Previous studies have shown that protected areas can successfully protect biodiversity over broad geographic areas, through empirical coarse-scale assessments of biodiversity at regional or global scales [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Protected areas (PAs) have been considered as a key to biodiversity conservation [1][2][3][4]. Previous studies have shown that protected areas can successfully protect biodiversity over broad geographic areas, through empirical coarse-scale assessments of biodiversity at regional or global scales [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes toward the protected area staff and the perceptions of management practices also affect people's attitudes (Ormsby andKaplin 2005, Allendorf 2007). For example, conflicts with managers due to resource extraction, strict rules on forest resources use, and access Shrivastava 2009, Shibia 2010), rude behavior (Ormsby and Kaplin 2005), or harassment by park rangers (Infield and Namara 2001) generate http://www.ecologyandsociety.org/vol16/iss3/art10/ negative attitudes toward protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…For example, conflicts with managers due to resource extraction, strict rules on forest resources use, and access Shrivastava 2009, Shibia 2010), rude behavior (Ormsby and Kaplin 2005), or harassment by park rangers (Infield and Namara 2001) generate http://www.ecologyandsociety.org/vol16/iss3/art10/ negative attitudes toward protected areas. Fear of resettlement and lack of job provision have the same impact (Allendorf 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally protected areas (PAs) have long represented a key conservation strategy in the face of rapid forest and biodiversity loss (Abakerli 2001;Nagothu 2003;Ormsby and Kaplin 2005;Clerici et al 2007;DeFries et al 2007) and are considered the most effective measure for conserving wild biodiversity in situ (Pimbert and Pretty 1997;Mulongoy and Chape 2004). Generally, PAs are 'areas especially dedicated to the protection and maintenance of biological diversity and associated cultural resources, which are managed through legal or other effective means' (IUCN 1994).…”
Section: Introductionmentioning
confidence: 99%